PEMBANGUNAN INFRASTRUKTUR DASAR BERKELANJUTAN DI KAWASAN PERBATASAN SEKITAR POS LINTAS BATAS NEGARA (PLBN) MOTAAIN, KABUPATE BELU, PROVINSI NUSA TENGGARA TIMUR - Eko Budi Santoso; Gatiningsih Gatiningsih; Dimas Widya Putra; Kholifah Nursa’diyyah RSP; Enjang Hidayat (Lembaga Riset dan Pengkajian Strategi Pemerintahan IPDN, 2025)
The development of border areas in the previous era was still based on the paradigm as backward that relatively under developed and isolated zone. However, since 2014 the paradigm has changed to be front yard, which was then followed by the development of many border areas, especially those with cross-border post (PLBN). One of them is the Motaain PLBN in Belu Regency, East Nusa Tenggara Province. This study aims to describe and assess the development of basic infrastructure to meet the basic needs of residents in the area around the Motaain PLBN. The method used was descriptive-evaluative qualitative research. Data collection techniques include interviews, observation, and documentation. Interviews were conducted with the Belu Regency government, the Motaain PLBN management, environmental officials, community leaders and ordinary people. The analysis technique used was narrative displays assisted by various maps (cartographs) and tables to describe the factual conditions that occur, and with the help of standards for assessing the condition of its fulfillment. The basic infrastructure in question includes social infrastructure and physical infrastructure. The research results show that social infrastructure has been well developed, but basic physical infrastructure, particularly clean water, sanitation, and drainage, is not yet adequately provided, so that overall the provision of basic infrastructure supporting sustainable living is considered inadequate. Several intergovernmental and sectoral collaborations are recommended, especially in the provision of basic physical infrastructure for clean water, which affects the fulfillment of sanitation needs of communities in border areas.